IMPLEMENTASI NILAI-NILAI JURNALISTIK DALAM PENULISAN BERITA DI INTRANET SEBAGAI MEDIA INTERNAL PT.PERTAMINA (PERSERO) REFINERY UNIT II DUMAI - Aulia Putri Rama; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Intranet is an internal media owned by PT. Pertamina (Persero) Refinery Unit II Dumai based online. Within the Intranet there is information and news about the company's policies and activities which in the process are carried out by Communications and Relations Section, Team Media Support exactly. News published is the result of coverage by Team Media Support. Thus this study aims to find out how Implementation of Jurnalistic Values in News Writing at Intranet as Internal Media PT. Pertamina (Persero) Refinery Unit II Dumai.This research uses descriptive method qualitative, data collecting technique using observation, in-depth interview and documentation. The informants were chosen by purposive sampling by selecting informants based on certain characteristics, the informant consisted of Head of Communication and Relations, Junior Officer Communication and Relations, Personnel of Team Media Support, and three employees as news reading on Intranet. Data analysis technique using data analysis by Miles and Huberman models.The results of this study show that : 1). Team Media Support has implemented reports/ direct observations in the coverage, but not all coverage is accompanied by interviews and there is also no literature research. 2). For news writing, Team Media Support has not fully understood how to writing a news with news values. 3). For news editing techniques that have been done by the right people and competent, but the efficiency time of editing is still not right because only the Head of Communications and Relationship can does, so that there are some news that has been written can not be published on the same day. 4). The main constraining factor in the implementation is the lack of competent human resources in the field of journalism, while the supporting factor is the Intranet has played an appropriate role as the company's internal media, because with the Intranet dissemination of information more effective and environmentally friendly.Keywords: Journalistic, News Writing, Internal Media, Intranet